Certolizumab-Induced Urticarial Vasculitis: A Case Report - Ouni, Bouraoui; Chahed, Ferdaous; Slim, Raoudha; Dridi, Baheddine; Sassi, Malek; Sriha, Badereddine; Ghariani, Nedia; Bensayed, Nesrine; Fathallah, Neila (Current Drug Safety, 2025)
<span class=
Keywords: pharmacovigilance